Reforma a vapor do metano para produção de hidrogênio: estudo termodinâmico e protótipo de modelo matemático de reator com membrana - Alves, Sandro de Carvalho (2005)
Methane steam reforming is the main industrial process for the production of hydrogen. The reaction should be carried out at high temperatures in order get reasonable conversions because of high endothermicity. Due to the continuous withdrawal of hydrogen from the membrane reactor the reforming temperatures are relatively lower. In this work, the results show the potential use of membrane reactors for hydrogen production from methane steam reforming with conditions more moderate than the conventional technology. This could result in an energy economy. The main goal of this dissertation was to present and to validate a model of reactor with a selective membrane to H2 incorporated in such system. Besides, thermodynamic and kinetic studies were accomplished for the steam reforming reactions. The experimental data used in the validation were obtained from literature and three mathematical models were presented. The first model is relatively simple, but representative of membrane reactor to methane reforming, where it considered only mass balance. These conditions are valid for laboratory scale where the reactor could be considered isothermic. From this first model a second model was proposed. This second model was more complex than the first because it considered the mass, energy and momentum balances along of reactor without membrane. The third model as the second model considered the mass, energy and momentum balances along of reactor but in this case the reactor has a membrane. These studies verified that variables as the hourly space velocity (WHSV), load-to-surface ratio (L/S), temperature, reaction pressure, hydrogen partial pressure and the membrane influenced significantly on the methane conversion. The influences of some parameters of the model were also analyzed through sensitivity studies by derivative methods by the code DASPK 3.0. For by the first model presented was analyzed the sensitivity to the perturbations of the parameter WHSV and L/S along of the reactor, in the methane conversion. The efect was more accentuated in the parameter L/S.